PENGEMBANGAN NILAI-NILAI DEMOKRASI DI SEKOLAH - Ok. M. Daniel Syahindra (Sekolah Tinggi Agama Islam Sumatera Medan, 2019)
The development of democratic values in schools needs to be applied to face the era of globalization which is now believed to bring a lot of global changes along with the acceleration of the entry and exit of various new cultures and civilizations from various nations in the world. That means, the world of education in printing qualified and professional human resources must prepare a democratic generation, so that it has a strong resistance in the midst of civilizational conflict. An interesting concrete step to be realized together, especially by educators and parties involved in the world of education, is to create a space for living and educational practice as a real life.